Cimmerian metamorphism and post Mid-Cimmerian exhumation in Central Iran: Insights from in-situ Rb/Sr and U/Pb dating. (1st August 2022) - Gyomlai, Thomas; Agard, Philippe; Jolivet, Laurent; Larvet, Tiphaine; Bonnet, Guillaume; Omrani, Jafar; Larson, Kyle; Caron, Benoit; Noël, Julie
Highlights: Coupled in-situ Rb/Sr and U/Pb dating allows to constrain metamorphic terranes evolution. Iran was affected by a Jurassic collisional metamorphism related to the Paleotethys closure. Metamorphic terranes are exhumed from ∼170 Ma onward in a context of upper plate extension. Abstract: The pre-Alpine evolution of the Tethyan domains between Gondwana and Laurasia, and in particular that of the Cimmerian continental blocks, remains poorly constrained. Central Iran is a key area to constrain the closure of the Paleotethys and the collision of Laurasia with the Cimmerian blocks drifted from Gondwana. The present study provides a combined metamorphic and geochronologic approach focused on two areas of Central Iran: the Kashmar-Kerman Tectonic Zone (KKTZ) and the Jandaq area, whose tectonometamorphic units are affected low- to middle-pressure high-temperature metamorphism. We performed in-situ texturally constrained U/Pb dating on titanite and Rb/Sr dating on mica to quantify the timing and intensity of burial and exhumation of these metamorphic rocks. Results show that metamorphism in the central and eastern KKTZ (7–9 kbar; ∼700 °C) is synchronous or slightly postdates the Cimmerian orogeny (∼190-180 Ma) and relates to the collision following the Paleotethys closure, whereas metamorphism in the Jandaq complex (12–13 kbar; ∼450 °C) relates to the Paleotethys subduction. Based on paleogeographic reconstructions, the KKTZ lied hundreds of kilometers south of the Paleotethys suture zone. As such, we propose that metamorphism along the KKTZ results from the closure and shortening of a rheologically weak domain located outboard of the main suture. In-situ Rb/Sr dating of biotite yields precise and accurate cooling ages (±2-5 Ma) ranging from 170 to 140 Ma. These cooling ages document the exhumation of these terranes from the Mid-Cimmerian event onward (∼170 Ma), coeval with the widespread extension distributed across Iran and thought to reflect upper plate extension above the Neotethyan subduction system.